Lanadelumab demonstrates rapid and sustained prevention of hereditary angioedema attacks. Issue 11 (6th July 2020) - Riedl, Marc A.; Maurer, Marcus; Bernstein, Jonathan A.; Banerji, Aleena; Longhurst, Hilary J.; Li, H. Henry; Lu, Peng; Hao, James; Juethner, Salomé; Lumry, William R.; ,
Abstract: Background: Lanadelumab demonstrated efficacy in preventing hereditary angioedema (HAE) attacks in the phase 3 HELP Study. Objective: To assess time to onset of effect and long‐term efficacy of lanadelumab, based on exploratory findings from the HELP Study. Methods: Eligible patients with HAE type I/II received lanadelumab 150 mg every 4 weeks (q4wks), 300 mg q4wks, 300 mg q2wks, or placebo. Ad hoc analyses evaluated day 0‐69 findings using a Poisson regression model accounting for overdispersion. Least‐squares mean monthly HAE attack rate for lanadelumab was compared with placebo. Intrapatient comparisons for days 0‐69 versus steady state (days 70‐182) used a paired t test for continuous endpoints or Kappa statistics for categorical endpoints. Results: One hundred twenty‐five patients were randomized and treated. During days 0‐69, mean monthly attack rate was significantly lower with lanadelumab (0.41‐0.76) vs placebo (2.04), including attacks requiring acute treatment (0.33‐0.61 vs 1.66) and moderate/severe attacks (0.31‐0.48 vs 1.33, all P ≤ .001). More patients receiving lanadelumab vs placebo were attack free (37.9%‐48.1% vs 7.3%) and responders (85.7%‐100% vs 26.8%). During steady state, the efficacy of lanadelumab vs placebo was similar or improved vs days 0‐69. Intrapatient differences were significant with lanadelumab 300 mg q4wks for select outcomes. Lanadelumab efficacy was durable—HAE attack rate was consistently lower vs placebo, from the first 2 weeks of treatment through study end. Treatment emergent adverse events were comparable during days 0‐69 and 70‐182. Conclusion: Protection with lanadelumab started from the first dose and continued throughout the entire study period. Abstract : During days 0‐69, lanadelumab‐treated patients had a significantly lower mean monthly hereditary angioedema (HAE) attack rate vs placebo and were more likely to be responders and attack free. Protection starts early and is sustained; during steady state, lanadelumab efficacy was similar or improved vs days 0‐69. Prophylactic agents with rapid onset, sustained effect, and convenient dosing frequency can improve HAE management plans. Abbreviations: HAE, hereditary angioedema; q2wks, every 2 weeks.